Translator’s Activity and the Italian Literary Canon in Poland: Waleria Marrené- Morzkowska and Zofia Ernstowa - Miszalska, Jadwiga (Porównania, 2020)
Waleria Marrené-Morzkowska (1832-1903), writer, journalist and translator, and Zofia Ernstowa (1918-1994), author of several dozen translations from Italian literature, were active in two (distinct) historical moments that were not easy for the Polish culture. During the partitions as well as in the times of the Polish People’s Republic many cultural initiatives were undertaken thanks to the determination of individuals. The archival materials preserved in Italy allow to reconstruct their microhistory, contacts with the Italian writers and activities in Poland that aimed at printing the selected works, constituting proof that the translator’s agency is not limited to execution of the commissions but often involves active participation in selecting the works for translation in order to create a literary canon.